Imaging features of bilateral vestibular neuritis - Kozić, Duško; Lemajić-Komazec, Slobodanka; Bjelan, Mladen; Boban, Jasmina; Sotirović-Seničar, Slavica; Kostić, Dejan (Vojnosanitetski pregled, 2021)
Abstract Introduction. The magnetic resonance imaging (MRI) was found to be insensitive diagnostic modality in detecting the abnormalities in patients with vestibular neuritis. Case report. A 32-year-old man was admitted to hospital with clinical signs of acute vestibular neuritis. The conventional MRI was inconclusive, including 3 mm slice-thickness postcontrast study, while the postcontrast high resolution study with 1 mm slice-thikness, detected bilateral enhancement of the vestibulocochlear nerve’s vestibular branch, consistent with inflammation. Conclusion. High-resolution 1 mm or submilimeter slices should be perfomed to evaluate patients with vestibular neuritis in order to increase the MRI sensitivity and improve correlation with clinical findings.